Indications for permanent pacing in dogs and cats - Santilli, R.A. (J Vet Cardiol, 2019)
Pacemaker implantation is considered as a standard procedure for treatment of symptomatic bradycardia in both dogs and cats. Advanced second-degree and third-degree atrioventricular blocks, sick sinus syndrome, persistent atrial standstill, and vasovagal syncope are the most common rhythm disturbances that require pacing to either alleviate clinical signs or prolong survival. Most pacemakers are implanted transvenously, using endocardial leads, but rarely epicardial leads may be necessary. To decide whether a patient is a candidate for pacing, as well as which pacing modality should be used, the clinician must have a clear understanding of the etiology, the pathophysiology, and the natural history of the most common bradyarrhythmias, as well as what result can be achieved by pacing patients with different rhythm disturbances. The goal of this review was, therefore, to describe the indications for pacing by evaluating the available evidence in both human and veterinary medicine. We described the etiology of bradyarrhythmias, clinical signs and electrocardiographic abnormalities, and the choice of pacing modality, taking into account how different choices may have different physiological consequences to selected patients. It is expected that this review will assist veterinarians in recognizing arrhythmias that may require permanent pacing and the risk-benefit of each pacing modality and its impact on outcome.